T-Cell Receptor Therapy in the Treatment of Ovarian Cancer: A Mini Review - Wu, Jessica W. Y.; Dand, Sudiksha; Doig, Lachlan; Papenfuss, Anthony T.; Scott, Clare L.; Ho, Gwo; Ooi, Joshua D. (Frontiers in Immunology, 2021)
Ovarian cancer, in particularly high grade serous ovarian cancer (HGSOC) and ovarian carcinosarcoma (OCS), are highly aggressive and deadly female cancers with limited treatment options. These tumours are generally unresponsive to immune check-point inhibitor (ICI) therapy and are referred to as immunologically “cold” tumours. Cell-based therapy, in particular, adoptive T-cell therapy, is an alternative immunotherapy option that has shown great potential, especially Chimeric antigen receptor T cell (CAR-T) therapy in the treatment of haematologic malignancies. However, the efficacy of CAR-T therapy in solid tumours has been modest. This review explores the potential of another cell-based therapy, T-cell receptor therapy (TCR-T) as an alternate treatment option for immunological “cold” OC and OCS tumours.